Settlements and appeals in the European Commission's cartel cases: An empirical assessment - Michael Hellwig; Kai Hüschelrath; Ulrich Laitenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
The introduction of the European Union (EU) Settlement Procedure in 2008 aimed at promoting the procedural efficiency of cartel investigations by the European Commission (EC). We use a data set consisting of 579 firms groups convicted by the EC for cartelization from 2000 to 2015 to investigate the impact of the settlement procedure on the probability to file an appeal. Based on the estimation of a model of the firm's decision to appeal in the presettlement era, we subsequently run out-of-sample predictions to estimate the number of hypothetical appeals cases in the settlement era absent the settlement procedure. Our findings of a settlement-induced reduction in the number of appeals of up to 55 percent allow the conclusion that the introduction of the settlement procedure generated substantial additional benefits to society beyond its undisputed key contribution of a faster and more efficient handling of cartel investigations by the EC.
Keywords: K21; L41; 330; antitrust policy; cartels; settlements; appeals; ex-post evaluation; European Union